2022
DOI: 10.1186/s13014-022-02064-9
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative locoregional recurrence pattern and treatment management of stage pT4 sigmoid colon cancer: a retrospective cohort study

Abstract: Background This study aimed to explore the pattern of locoregional recurrence after surgery in patients with non-metastatic stage pT4 sigmoid colon cancer and the role of adjuvant radiotherapy on survival. Methods We retrospectively analyzed data from 208 patients who underwent surgery in our hospital. The patients were randomly divided into training and validation groups at a 1:1 ratio. Patients at high risk for locoregional recurrence were screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Existing data previously identified various prognostic variables influencing disease recurrence in colorectal cancer patients undergoing curative resection [18][19][20]. PNI has been linked to higher recurrence rates in stage I-III colorectal cancer patients treated with curative intent, according to a study by Holt et al [18].…”
Section: Discussionmentioning
confidence: 99%
“…Existing data previously identified various prognostic variables influencing disease recurrence in colorectal cancer patients undergoing curative resection [18][19][20]. PNI has been linked to higher recurrence rates in stage I-III colorectal cancer patients treated with curative intent, according to a study by Holt et al [18].…”
Section: Discussionmentioning
confidence: 99%
“…Existing data previously identi ed various prognostic variables in uencing disease recurrence in colorectal cancer patients undergoing curative resection [15][16][17]. PNI has been linked to higher recurrence rates in stage I-III colorectal cancer patients treated with curative intent, according to a study by Holt et al [15].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy (RT) is not widely used in CC, because of the uncertain position and small bowel toxicity, but may be considered in certain clinical scenarios. Patients with stage T4 disease had a high likelihood of locoregional recurrence,5 and perhaps locoregional RT could reduce the recurrence. A small sampled study had shown that patients with pT4b disease receiving adjuvant chemoradiotherapy enhanced locoregional control and DFS 6.…”
Section: Introductionmentioning
confidence: 99%